Evaluación técnico-financiera de la inyección de una enzima biológica como método de recobro mejorado de petróleo para el pozo H2 del campo Llanos 28 (2018)
The Llanos 28 field is located in the Cuenca de los Llanos Orientales in the department of Casanare, in the municipality of Orocué, in this project several scenarios were studied where the company requested a study of the biological enzyme injection as an EOR method or improved recovery, this is in order to increase oil production to have higher income. Results were obtained to carry out the study, continuing with a description where the process of injection of the enzyme is specified, then the simulation model is presented as project validation. Consequently the technical and financial evaluation is carried out, in which criteria based on theoretical and practical values are contemplated for each proposed scenario and based on the information collected, a classification of the simulations is carried out, which determines which of these is the most feasible scenario to implement.